Evaluating Public Awareness of Glaucoma and Their Associated Risk Factors in Obio/Akpor Local Government Area, Rivers State - Onwunali Juliet Chinwendu; Imarenezor Edobor Peter Kenneth; Efere Y. Samson (Darul Yasin Al Sys, 2026)
Glaucoma is a progressive eye disease and a leading cause of irreversible blindness worldwide, often developing without early symptoms, which makes timely detection and treatment crucial for reducing vision loss. This study assessed the level of glaucoma awareness and knowledge of its risk factors among adults in Obio/Akpor Local Government Area, Rivers State, Nigeria, and explored barriers to accessing eye care. A cross-sectional survey was conducted among 440 consenting adults aged 18 years and above using a standardized questionnaire to collect socio-demographic characteristics, awareness of glaucoma, knowledge of its severity and risk factors, and willingness to seek eye care. The sample comprised 60.9% females and 39.1% males with diverse employment and educational backgrounds. While 85.7% of respondents had heard of glaucoma and many recognized it as a cause of blindness, only 26.6% knew it could be asymptomatic, and detailed knowledge of its severity profile and risk factors was limited; the main sources of information were health workers (34%), schools/lectures (24.5%), and radio/television (18.9%). A large proportion expressed willingness to undergo free eye screening, yet lack of health insurance emerged as a notable barrier to accessing timely care. These findings indicate that general awareness of glaucoma in the community is not matched by adequate understanding of its silent progression and risk factors, potentially delaying care-seeking behavior. The study concludes that awareness campaigns alone are insufficient and that comprehensive public health education, stronger collaboration between healthcare providers and community organizations, and improved access to routine vision screening are essential to promote early detection and effective management of glaucoma, particularly among high-risk populations in Obio/Akpor and similar settings.